Unmet Healthcare Needs in People with Disabilities: Comparison with the General Population in Korea - Hwang, Byungkwan (Korean Academy of Rehabilitation Medicine, 2011)
OBJECTIVE: To determine the degree of disparity in unmet healthcare needs between people with disabilities and the general population in South Korea, and to analyze their perspective reasons. METHOD: Survey results of 9,744 subjects that participated in the 4(th) Korea National Health and Nutrition Examination Survey and 7,000 people that participated in the 2008 Survey of Disabled people were used in this population-based cross-sectional study. Unmet healthcare needs were identified as reporting experience during the last 12 months when there was a need to see a doctor, but were unable to get it. We assessed unmet healthcare needs by demographic variables, social variables and characteristics of disability. Chi-square test and logistic regression were used to determine which variables were related to unmet healthcare needs. RESULTS: A total of 22.1% of people with disabilities and 22.8% of the general population had unmet healthcare needs. However, brain impairment (25.3%) and physical impairment (25.2%) had more unmet healthcare needs than the general population and other disabilities. Unmet healthcare needs of people with disabilities was related to sex, age, self-perceived health, marital status, income, occupation and category of disability. Whereas the reasons for unmet healthcare needs in people with disabilities were lack of money (57.3%) and inaccessible transportation (12.8%), those for the general population were no available time (30.2%) and mild symptoms (23.8%). CONCLUSION: Brain and physical impairment cases with limitations to accessible transportation had the higher unmet healthcare needs. In addition, the reasons for people with these disabilities were more environmental than those of the general population.